A short review on novel anti-malarial Heterocyclic aromatic therapeutic agents: synthesis, efficacy and effectiveness of potential drug candidates for malaria - Mondal, Anupam (Brac University, 2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.